Materials for Buildings and Structures 2000
DOI: 10.1002/3527606211.ch3
|View full text |Cite
|
Sign up to set email alerts
|

Economic Design and Construction with Structural Lightweight Aggregate Concrete

Abstract: Introduction BackgroundLightweight aggregate concrete (LWAC) has potential to offer weight reduction without significantly having to compromise the structural properties. Still, however, this material has not realized its potential as a commonly accepted alternative to normal weight concrete (NWC) or other construction materials. Main reasons for this are somewhat higher material and production costs, a common skepticism related to production properties, design/structural performance and durability, and the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…It is important here to mention that utilizing the LWCA was only for a structural purpose and not for its thermal behaviour. (Clarke, 2002;Hammer et al, 2005).…”
Section: Which Sources Are Investigated To Identify These Technologies?mentioning
confidence: 99%
“…It is important here to mention that utilizing the LWCA was only for a structural purpose and not for its thermal behaviour. (Clarke, 2002;Hammer et al, 2005).…”
Section: Which Sources Are Investigated To Identify These Technologies?mentioning
confidence: 99%
“…It is important here to mention that utilizing the LWCA was only for a structural purpose and not for its thermal behaviour. (Clarke, 2002;Hammer et al, 2005).…”
Section: Which Sources Are Investigated To Identify These Technologies?mentioning
confidence: 99%
“…Several studies (Nahhab and Ketab, 2020;Nepomuceno, 2018;Ismail and Halim, 2020;Muñoz et al, 2018) found that the properties of mortars and concretes containing ECA depend on the size and shape of aggregate. The use of ECAs with different quantities and combinations in the production of concrete is possible and represents a potential alternative to conventional concrete (Rumsys et al, 2018;Bogas et al, 2012;Bogas et al, 2012;Hubertova and Hela, 2013;Lee et al,2019;Hammer et al, 2000). However, few studies focused on the effect of expanded clay aggregate size on concretes and the resistance of this concrete to freeze-thaw cycles.…”
Section: Introductionmentioning
confidence: 99%